2004
DOI: 10.1109/tns.2004.823331
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Observer Study for the Evaluation and Optimization of Compensation Methods for Myocardial SPECT Using a Phantom Population That Realistically Models Patient Variability

Abstract: The goal of this study was to develop and apply a population of phantoms that realistically models patient variability and use it to optimize and evaluate different compensation methods used during reconstruction process with respect to defect detection in myocardial SPECT images. Various combinations of attenuation, detector response and scatter compensation were used in this study. A major difference between this and previous studies was that the level of realism was significantly increased by inclusion of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 15 publications
3
64
0
3
Order By: Relevance
“…Anthropomorphic phantoms have been implemented in other imaging modalities and have been used to demonstrate that simple, nonanthropomorphic phantoms produce misleading results when used to optimize imaging systems. 24,[57][58][59] The phantom described in this work will provide a much-needed platform for better understanding the interaction of breast MRI acquisition parameters with lesion detection and estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropomorphic phantoms have been implemented in other imaging modalities and have been used to demonstrate that simple, nonanthropomorphic phantoms produce misleading results when used to optimize imaging systems. 24,[57][58][59] The phantom described in this work will provide a much-needed platform for better understanding the interaction of breast MRI acquisition parameters with lesion detection and estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Breast anatomy is composed of interlacing fat-and water-containing tissues that produce imaging artifacts ͑e.g., chemical shift artifact͒ and can hinder lesion detectability. The importance of realistic phantom structure in the evaluation of imaging systems for the purpose of abnormality detection was demonstrated in a study by He et al, 24 in which both phantom and patient data were used to perform reader studies evaluating compensation methods for myocardial SPECT image reconstruction algorithms. They found that phantoms with more complicated, realistic image structures resulted in performance measures for defect detection that more closely matched results derived from patient data than studies with more simplistic phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…The channelized hotelling observer (CHO) has been previously validated with human observer studies and showed good agreement with the human observers in a variety of applications. [17][18][19][20] However, using the CHO for optimizing acquisition parameters requires reconstruction of a large number of projection data and optimization of various reconstruction and regularization parameters (e.g., iteration number and cutoff frequency of smoothing filters). Thus, using an observer that performs directly on projection data is computationally less expensive than an observer that performs on reconstructed images (e.g., the CHO).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 These channel sets have been used in several cardiac studies and shown good correlation with human observer performance. [13][14][15][16] The spatial domain templates were obtained by taking the inverse Fourier transform of the four channels in frequency domain and shifting the template centers to the defect centroid. For each reconstructed and resliced image, a four-element feature vector was obtained by taking the dot product of the extracted image and the spatial domain templates for each channel.…”
Section: Iib2 Application Of the Chomentioning
confidence: 99%